Properties of Foamed Gel for Coal Ignition Suppression in Underground Coal Mine. Issue 8 (3rd August 2019) - Guo, Qing; Ren, Wanxing; Bai, Lei
ABSTRACT: Foamed gel was developed as efficient material for coal ignition control in fire-prevention techniques. The preparation process, structure, key equipment, stability and inhibiting effect of foamed gel are experimentally studied. Foamed gel possesses three-dimensional net structures, consisted of gel particles and aqueous foam. Foaming device is the key equipment that could generate foam and gel simultaneously. In addition, the half-life of foamed gel is beyond 24 h, which is more than six-folders of foam. The "strong-node and weak-rod" structure formed by gel particles is the key reason enhancing the stability of foamed gel. Further, by using coal spontaneous combustion apparatus, the inhibiting effect of foamed gel is conducted by testing the release of CO. The results show that the inhibiting rate of foamed gel is 73.72%, higher than CaCl2 with 57.35% in 100°C. Meanwhile, field application in coal mine suggests that foamed gel can effectively suppress coal fire in gobs.